Comparative effectiveness of different surgical timings on neurological outcomes for cranioplasty: Protocol for a prospective non-randomized controlled trial - Jingguo Yang; Xingyu Zhang; Xiaoyu Yang; Junjie Wang; Chao You; Lu Ma; Junwen Guan (PLoS ONE, 2025)
Background Cranioplasty (CP), a surgical procedure that restores cranial integrity and potentially enhances neurological outcomes, is commonly performed following decompressive craniectomy for various reasons. However, there is considerable controversy and variation regarding the optimal timing for cranioplasty, particularly concerning its impact on neurological functional outcomes. This paper outlines the protocol for a multicenter, non-randomized controlled trial designed to investigate whether the timing of cranioplasty influences neurological outcomes. Methods/Design This study will be conducted from June 2025 to June 2026 across multiple clinical centers in China, targeting the enrollment of at least 500 adults aged 18-65 years with skull defects larger than 25 cm². Participants will be divided based on the timing of their cranioplasty relative to decompressive craniectomy into two groups: early (within 3 months post-decompression) and late (after 3 months). The primary outcome, assessed through the Barthel Index, will measure functional recovery 6 months post-surgery, with secondary outcomes including mortality, quality of life, cognitive performance and complication rates. Discussion This non-randomized clinical trial focuses on the neurological outcomes associated with different timings of cranioplasty. It is anticipated that the findings will contribute valuable insights and support more informed clinical decisions regarding the timing of cranioplasty. By comparing early and late cranioplasty, the trial aims to clarify how timing affects recovery and overall neurological improvement post-surgery. Trial Registration: ChiCTR2400094619